INFORMATION SYSTEM OPTIMIZATION COMPUTER BASED: ANALYZING THE ROLE OF THE OPERATING SYSTEM, SERVER INFRASTRUCTURE, AND PROGRAMMERS - Ade Setiawan; Neni Nuraeni; Hadi Supratikta (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
This qualitative research examines the optimization of computer-based information systems by examining the important roles of operating systems, server infrastructure, and programmers. The study aims to understand how these three components interact and contribute to the improvement of information system performance. Through an in-depth analysis of literature and related theories, this study presents the findings that an efficient operating system can improve security and performance, a reliable server infrastructure supports scalability and availability, and qualified programmers are essential in system development and maintenance. The results of this study show that the synergy between operating systems, server infrastructure, and programmers is a key factor in achieving information system optimization. The resulting recommendations focus on strategies to effectively integrate these three components, with the aim of supporting managerial decisions in the development of better information systems